Cuticular Ridge Pattern in Ostertagia gruehneri and Ostertagia arctica (Nematoda: Trichostrongyloidea) from Caribou, Rangifer tarandus - Lichtenfels, J. Ralph; Pilitt, P. A.; Fruetel, M. (DigitalCommons@University of Nebraska - Lincoln, 1990)
Two species of medium stomach worms are common parasites of the caribou, Rangifer tarandus. The two species, Ostertagia gruehneri Skrjabin, 1929, and O. arctica Mitzkewitzsch, 1929, differ so markedly in morphology of the spicules and genital cone that many nematode systematists place them in different genera. Recent studies of similar pairs of species parasitic in other ruminants have provided evidence that such pairs of species may be morphotypes of one species. The two species from caribou are redescribed with emphasis on the pattern of surface cuticular ridges and the structure of the esophagus, characters considered useful for distinguishing species of trichostrongyloid nematodes. Ostertagia gruehneri and O. arctica were found to have identical ridge patterns and esophageal characteristics. Both species had five lateral ridges, a long eosphageal valve, and ducts for the subventral esophageal glands that opened internally posterior to the level of the cervical papillae.